Multiple Angle of Bisector Rinn Holder for Oral X-Ray - Amirul Khalid Bin Nik Dziauddin, Nik; Fazli Adull Manan, Nor; Yusmialdil Putera Mohd Yusof, Mohd; Mahmud, Jamaluddin; Azam Abdullah, Shahrul (International Journal of Engineering and Technology, 2018)
Multiple angle of bisector rinn holder is a film holder instrument that is yet to be developed that is able to use paralleling technique and bisecting angle technique in oral x-ray radiography. It is a device aimed to be able to use multiple techniques in oral radiography while getting a good image quality that helps the dentist in doing their work. This is a project that involves the development of the instruments and the effectiveness of the instruments compared to the existing one. The result of the radiographic image was compared and certain constraint was used to compare the instruments with the existing instruments. This project used CATIA V5 software for the design stage. In this project, the instrument was tested to validate the effectiveness where the testing was conducted at the faculty of dentistry. The outcome was the effectiveness of the instrument as compared to the existing instrument with other certain constraints.Â Â